Conceptualizing stigma in contexts of pregnancy and opioid misuse: A qualitative study with women and healthcare providers in Ohio. (1st May 2021) - Syvertsen, Jennifer L.; Toneff, Hannah; Howard, Heather; Spadola, Christine; Madden, Danielle; Clapp, John
Highlights: Stigma shapes access and quality of care among pregnant women who use opioids. Qualitative interviews with women and healthcare providers reveal experiences of stigma. Structural, enacted, anticipated, and internalized stigma shape women's healthcare. Concerns about neonatal abstinence syndrome (NAS) intensify stigma. Harm reduction approaches are recommended to reduce stigma. Abstract: Background: Women with histories of opioid misuse face drug-related stigma, which can be amplified during pregnancy. While women are often blamed for their drug use and urged to change, the social contexts that create and reinforce stigma are largely unchallenged. Drawing on a multidimensional model of stigma, we examine how stigma manifested across women's pregnancy journeys to shape access and quality of care. Methods: We triangulate in-depth interviews with 28 women with histories of opioid misuse who were pregnant or recently gave birth and 18 healthcare providers in Ohio. Thematic analysis examined how stigma operates across contexts of care. Results: Providers represented physicians, nurses, social workers, counselors, and healthcare administrators. Among 28 women, average age was 30 (range: 22–41) and 79 % were White. Most women used prenatal medication-assisted treatment (MAT), including Suboxone (n = 19) or methadone (n = 8), and 15 were pregnant. Evidence of stigma emerged across healthcare contexts. Structural stigma encoded barriers to care in insurance practices and punitive drug treatment, while enacted stigma manifested as mistreatment and judgment from providers. Unpredictability of an infant diagnosis of neonatal abstinence syndrome (NAS), even when women were "doing everything right" by using MAT, perpetuated anticipated stigma from fear of loss of custody and internalized stigma among women who felt guilty about the diagnosis. Providers recognized the harmful effects of these stigmas and many actively addressed it. Conclusions: We recommend harm reduction approaches to address the multiplicity of stigmas that women navigate in opioid misuse and pregnancy to improve healthcare experiences.